2009
DOI: 10.1002/rcm.3953
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection and characterization of reactive drug metabolites in vitro using several isotope‐labeled trapping agents and ultra‐performance liquid chromatography/time‐of‐flight mass spectrometry

Abstract: Reactive metabolites are believed to be one of the main reasons for unexpected drug-induced toxicity issues, by forming covalent adducts with cell proteins or DNA. Due to their high reactivity and short lifespan they are not directly detected by traditional analytical methods, but are most traditionally analyzed by liquid chromatography/tandem mass spectrometry (LC/MS/MS) after chemical trapping with nucleophilic agents such as glutathione. Here, a simple but very efficient assay was built up for screening rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 33 publications
9
88
0
1
Order By: Relevance
“…Occasional cases of liver injury in patients treated with CLZ might be the result of local bioactivation to a reactive nitrenium ion by hepatic P450s (Maggs et al, 1995). In addition, bioactivation of CLZ to a reactive iminium ion, which can be trapped by cyanide, has been demonstrated in microsomal incubations (Argoti et al, 2005;Rousu et al, 2009;Li et al, 2011;Barbara and Castro-Perez JM, 2011) and might contribute to hepatotoxicity. Although these reactive CLZ metabolites have been demonstrated in many in vitro studies using HLM, only very limited information is available on the role of individual P450s in bioactivation of CLZ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occasional cases of liver injury in patients treated with CLZ might be the result of local bioactivation to a reactive nitrenium ion by hepatic P450s (Maggs et al, 1995). In addition, bioactivation of CLZ to a reactive iminium ion, which can be trapped by cyanide, has been demonstrated in microsomal incubations (Argoti et al, 2005;Rousu et al, 2009;Li et al, 2011;Barbara and Castro-Perez JM, 2011) and might contribute to hepatotoxicity. Although these reactive CLZ metabolites have been demonstrated in many in vitro studies using HLM, only very limited information is available on the role of individual P450s in bioactivation of CLZ .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, formation of iminium ions resulting from dehydrogenation of the piperazine-ring of CLZ, DMCLZ, and CLZ-NO were demonstrated using cyanide, which is able to trap hard electrophiles (Rousu et al, 2009;Argoti et al, 2005;Li et al, 2011, Barbara andCastro-Perez, 2011). Theoretically, two different iminium ions can be formed by dehydrogenation of the two different pairs of nitrogen-methylene bonds of the piperazine-ring (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…However, as only one mercapturate and GSH adduct [NVP-3-mercapturate (NVP-M2) and NVP-3-GSH (NVP-G2), respectively] was formed by HLM (Table 1), either the purely oxidative reactions of unsupplemented HLM fail to reproduce metabolic activation of NVP in vivo or HLM do not trap the reactive metabolite(s) with GSH or NAC via both the addition reactions that operate in vivo. A coincubation of HLM and GSH or a GSH derivative is now a standard preparation used in screens for reactive metabolites that are soft electrophiles (Gan et al, 2009), but it frequently yields more conjugates than can be accounted for in vivo (Bu et al, 2007;Rousu et al, 2009). NVP is an exception and emphasizes the need for whole animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…The task can be readily accomplished with HR-MS-based approached. Rousu et al reported a screening method utilizing stable isotope labeled GSH, KCN, and semicarbazide as trapping agents and TOF MS as analytical tool [30]. MDF processing of high resolution full MS data set provided unambiguous identification of both hard and soft reactive metabolites.…”
Section: Introductionmentioning
confidence: 99%